(untitled) (Journal of Face Aesthetics, 2019)
Hair loss is a common problem seen in dermatology. Both women and men are affected. Androgenetic alopecia is one of the most frequent type of hair loss observed in women. The diagnostic process is complex and includes different noninvasive procedures, laboratory tests and sometimes requires scalp biopsy. Trichoscopy is fairly new and useful diagnostic method that enables making the right diagnosis. Treatment of hair loss is often complicated and long‑lasting but in some cases it may be helpful to follow recommendations of various scientific boards. Here, we present a case of a woman with diffuse hair loss whose trichoscopic examination allowed to diagnose androgenetic alopecia.